Use of augmented reality in chromatography learning: How is this dynamic visual artifact fostering the visualization capacities of chemistry undergraduate students? - Cristian Merino; Cristian Merino; Ainoa Marzábal; Waldo Quiroz; Sonia Pino; Francisco López-Cortés; Ximena Carrasco; Brant G. Miller (Frontiers in Education, 2022)
Developing chemistry students' capability to use representations to explain phenomena is a challenging task for educators. To overcome chemistry students' learning difficulties, strategies that favor the development of visualization capabilities have been identified as productive. We are particularly interested in exploring the use of augmented reality in chemistry education to foster the development of those capabilities in undergraduate students. Our research objective was to analyze the contribution of augmented reality to support undergraduate chemistry students' visualization capacities while explaining the physical-kinetic processes of chromatography. Using an exploratory case study approach, we designed and conducted four task teaching and learning sequences, with seven Augmented Reality markers embedded. Thirty-eight undergraduate students, who voluntarily agreed to participate, explained the different elution rates of pigments in a chromatographic column. Their written accounts were analyzed to identify the level of sophistication of their representations. After using Augmented Reality, students' representations progressed from simple macroscopic descriptions of observed phenomena to explanations of processes where scientific ideas and microscopic representations were used as supporting evidence. Our study shows that the use of Augmented Reality has the potential to favor a more sophisticated use of representations when undergraduate students explain chromatographic processes. However, there are still limitations in reaching the highest levels of performance described in the literature.